2016
DOI: 10.1016/j.ijcard.2016.06.283
|View full text |Cite
|
Sign up to set email alerts
|

No benefit of additional treatment with exenatide in patients with an acute myocardial infarction

Abstract: Exenatide did not reduce myocardial infarct size expressed as a percentage of AAR in ST elevated myocardial infarction patients successfully treated with percutaneous coronary intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 24 publications
(33 reference statements)
1
19
0
Order By: Relevance
“…Importantly, the use of GLP-1 receptor agonists has appeared as one of the currently most promising approaches to pharmacologically limit ischemia-reperfusion injury after two trials demonstrating smaller infarct size and better left ventricular function in patients with STEMI by the administration of the GLP-1 receptor agonist exendin-4 as an adjunct to standard therapy including primary PCI 75,76 . Somewhat puzzling, a similar approach did not result in smaller infact size in another recent study 178 . Nontheless, in a rat model it was demonstrated that the GLP-1 receptor inhibitor exendin(9-39) abolishes RIC-induced cardioprotection 179 .…”
Section: The Glp-1 Receptor In Ricmentioning
confidence: 88%
“…Importantly, the use of GLP-1 receptor agonists has appeared as one of the currently most promising approaches to pharmacologically limit ischemia-reperfusion injury after two trials demonstrating smaller infarct size and better left ventricular function in patients with STEMI by the administration of the GLP-1 receptor agonist exendin-4 as an adjunct to standard therapy including primary PCI 75,76 . Somewhat puzzling, a similar approach did not result in smaller infact size in another recent study 178 . Nontheless, in a rat model it was demonstrated that the GLP-1 receptor inhibitor exendin(9-39) abolishes RIC-induced cardioprotection 179 .…”
Section: The Glp-1 Receptor In Ricmentioning
confidence: 88%
“…Although GLP1-RA are cardioprotective in patients with T2D and high cardiovascular risk, recent studies showed that GLP1 levels were increased in patients with acute MI and were correlated with an adverse outcome and early events ( Kahles et al, 2020 ). Different trials investigated the potential of liraglutide ( Chen et al, 2015 , 2016a , b ) and exenatide ( Kyhl et al, 2016 ; Roos et al, 2016 ) as a medication in patients presenting with non-ST-elevation MI (NSTEMI) and STEMI ( Table 2 ). A meta-analysis of trials enrolling acute MI patients with PCI (<26% T2D patients) confirmed the reduction in infarct size and improvement in LVEF by treatment with GLP1-RA compared to placebo ( Huang et al, 2017 ).…”
Section: Glucagon-like Peptide-1-mediated Cardioprotectionmentioning
confidence: 99%
“…This effect of exenatide was confirmed in an Asian population, since Woo et al observed an almost 50 % reduction in MI size when administered subcutaneously [ 263 ]. A recent clinical study has failed to demonstrate a cardioprotective effect with exenatide in STEMI patients—it is not clear why this study was neutral, but it may have been related to the dose used [ 208 ]. To date no trials have sought to challenge the results from the proof-of-concept studies on a clinical end point.…”
Section: Pharmacological Targeting Of Myocardial Irimentioning
confidence: 99%